Primary Motor Cortex Activation during Action Observation of Tasks at Different Video Speeds Is Dependent on Movement Task and Muscle Properties - Moriuchi, Takefumi; Matsuda, Daiki; Nakamura, Jirou; Matsuo, Takashi; Nakashima, Akira; Nishi, Keita; Fujiwara, Kengo; Iso, Naoki; Nakane, Hideyuki; Higashi, Toshio (Frontiers in Human Neuroscience, 2017)
The aim of the present study was to investigate how the video speed of observed action affects the excitability of the primary motor cortex, as assessed by the size of motor-evoked potentials induced by transcranial magnetic stimulation. Twelve healthy subjects observed a video clip of a person catching a ball (experiment 1: rapid movement) and another twelve healthy subjects observed a video clip of a person reaching to lift a ball (experiment 2: slow movement task). We played each video at three different speeds (slow, normal, and fast). The stimulus was given at two points of timing in each experiment. These stimulus points were locked to specific frames of the video rather than occurring at specific absolute times, for ease of comparison across different speeds. We recorded motor-evoked potentials from the first dorsal interosseous muscle (FDI) and abductor digiti minimi muscle (ADM) of the right hand. Motor-evoked potentials were significantly different for different video speeds only in the rapid movement task. Motor-evoked potentials for the rapid movement task were higher when subjects observed an action played at slow speed than normal or fast speed condition. There was no significant change for the slow movement task. Video speed was effective only in the ADM. Moreover, motor-evoked potentials in the ADM were significantly higher than in the FDI in a rapid movement task under the slow speed condition. Our findings suggest that the primary motor cortex becomes more excitable when subjects observe the video clip at the slow speed in a rapid movement, because they could recognize the elements of movement in others. Our results suggest the effects of manipulating the speed of the viewed task on the excitability of the primary motor cortex during passive observation differ depending on the type of movement task observed. It is likely that rehabilitation in the clinical setting will be more efficient if the video speed is changed to match the task’s characteristics.